Learning in creative tasks: Evidence from a digital platform - Jiatong Zhong (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2024)
This paper explores learning-by-doing in the context of creative tasks using detailed data on fiction writers from a digital publishing platform. I construct measures to quantify authors' performance over time and document significant variation in both starting levels and rates of improvement. Learning manifests as an improvement in quality instead of the speed of production. Quality improvement can last for several years, much longer than typically observed in manufacturing settings, and authors do not improve fastest at the beginning. These findings show that human capital accumulation has distinctive features in the context of creative and complex tasks, which institutions should consider in the training and evaluation of new workers in creative occupations.
Keywords: D83; J24; J46; L82; 330; learning by doing; learning curves; creative tasks